From Classical Kafā’ah to Contemporary Economic Justice: A Hadith-Based Legal Reassessment in Islamic Family Law - Nurdin, Zurifah; Suryani; Agusten (AL-ISTINBATH : Jurnal Hukum Islam, 2025)
This study aims to reassess the concept of economic kafa’ah by re-examining prophetic traditions (ahadith) through a phenomenological and socio-legal lens. Employing qualitative methodology, this research integrates thematic hadith analysis, historical contextualization of classical juristic opinions, and phenomenological interpretation to explore shifts in meaning and application. The findings reveal that economic kafa’ah in prophetic tradition primarily emphasizes ethical reliability, economic responsibility, and shared life capital rather than pre-existing wealth or social pedigree. Contemporary application suggests that kafa’ah is a dynamic construct that may emerge through mutual potential, education, work ethic, and long-term economic cooperation. The legal reassessment demonstrates that classical hierarchy-based criteria are not immutable; instead, they may be contextualized according to maqasid al-shari‘ah to promote economic justice, household stability, and gender balanced financial roles. This study concludes that economic kafa’ah should be reconstructed as a principle of equitable capability and shared socio-economic commitment rather than rigid material equivalence.